The Effectiveness of an Intervention Combination of Error Word Drill and Repeated Reading Using iPad Technology - O'Shea, Kaitlin M. (My University, 2013)
As schools adopt a Response to Intervention (RtI) framework, research in education and school psychology has increased its focus on exploring interventions to help struggling readers remediate their skills. At the same time, schools are becoming increasingly interested in investigating ways in which technology can be incorporated into their service delivery through curriculum, instruction, and intervention. The present study set out to explore these two areas of interest in education. The current study investigated whether combining the evidence-based interventions of Repeated Reading, which emphasizes practice, and Error Word Drill, which emphasizes feedback, produced greater gains in oral reading fluency when compared to the effects of the individual interventions for four elementary-aged students. The results suggested that the combination of the interventions did not significantly increase students' oral reading fluency when compared to using each intervention alone. In addition, the researcher was interested in exploring the students' perceptions of using iPads as part of intervention implementation. The results were mixed; two of the students found the iPad to be an acceptable component of the intervention, while the other two students did not prefer to use the iPad during the intervention. Limitations and suggestions for future research are discussed.
Keywords: Response to intervention (Learning disabled children); Reading (Elementary)--Remedial teaching; Reading (Elementary)--Computer-assisted instruction; Fluency (Language learning)--Computer-assisted instruction; Oral reading--Study and teaching (Elementary); Computer-assisted instruction--Evaluation; iPad (Computer)--Educational applications